Surface‐enhanced Raman spectra of the neonicotinoid pesticide thiacloprid. (23rd June 2013) - Cañamares, Maria Vega; Feis, Alessandro
Abstract : Thiacloprid is a widely used pesticide belonging to the neonicotinoid class, which is characterized by a selective activity against insects and a reduced acute toxicity for humans. The importance of the environmental impact of neonicotinoids is being intensively researched, in order to evaluate the danger they pose for useful insects. Physical methods which allow the characterization of neonicotinoids in diluted aqueous solutions are therefore desirable. We present a study of Raman and surface‐enhanced Raman scattering (SERS) spectroscopy on thiacloprid in solid state, in acetone solution, and adsorbed onto silver and gold hydrosols at μM concentration. Density functional theory calculations allow the individualization of the most stable molecular structure, both in gas phase and in solution, and of the corresponding Raman spectra. The vibrational assignments lead to an interpretation of the differences between SERS and ordinary Raman spectra based on the possible interactions between the molecule and the metal surface, the main one involving the iminocyano group. Formation of a charge‐transfer complex is suggested by the dependence of the SERS spectra on the laser excitation wavelength. We evaluate the applicability of SERS spectroscopy to the chemical analysis of thiacloprid comparing SERS with current analytical methods. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : A comprehensive study about the Raman and surface‐enhanced Raman scattering features of the widespread insecticide thiacloprid is presented. A complete vibrational assignment and models for the interaction with the metal surface are proposed.